Dorsal onlay buccal mucosal graft or penile skin graft substitution urethroplasty in bulbar urethral stricture: compare the outcome and review - Khandelwal, Atul K. (International Surgery Journal, 2020)
Background: Authors describe their experience with dorsal onlay urethroplasty using Buccal mucosal graft or penile skin graft through dorsal sagittal urethrotomy for bulbar urethral stricture. Methods: From 2014 to 2017, 29 male patients with bulbar urethral stricture have been treated by one stage dorsal onlay substitution urethroplasty using buccal mucosal graft and penile skin graft. Patients with balanitis xerotica obliterans, unhealthy penile skin, oral mucosa pathology or those who had undergone more than one urethral dilation/internal urethrotomy or urethroplasty were excluded from study. Results were analyzed at 6th and 12th month follow up with clinical history and uroflowmetry. Clinical outcome was considered a failure when any postoperative instrumentation was needed, including dilation or optical internal urethrotomy. Results: A total of 16 men age between 21 to 56 years for buccal mucosa graft (BMG) urethroplasty and 13 men age between 18 to 59 years underwent dorsal onlay substitution urethroplasty using BMG and penile skin graft (PSG). Mean stricture length was 4.2 cm (3.8-6) for BMG urethroplasty and 4.1 cm (3.2-5) for PSG urethroplasty. Mean length and width of graft were 4.2 cm and 2.6 cm respectively in BMG urethroplasty while 4.6 cm and 2.5 cm in PSAG urethroplasty. Average follow up months were 13.4 months with overall success rate 87.5% in BMG urethroplasty while average follow up months were 14.6 months with overall success rate 82.3% in PSG urethroplasty. Conclusions: On short term follow up substitution urethroplasty using both penile skin and buccal mucosa graft have comparable results.